Definitions of the term ″monitoring″ in the terminological system of pedagogy based on the construction of a generic-specific network - Bondarenko, T. (Problems of Engineer-Pedagogical Education, 2019)
In the article, the problem of semantic relations of the term “monitoring” in the terminological system of pedagogy is tackled by means of a terminological analysis. The problem is solved by building a genericspecific network of concepts, which reflects only the nearest generic-specific relations. On the basis of a detailed analysis of the views of various researchers on the nature and essence of the concept of “monitoring,” its related term, which is “observation”, is determined and proved to be at the root of the constructed network. At the next levels of the network, a genetic-specific group of concepts of “pedagogical monitoring” is formed. This group is characterized by subordination to the general generic concept, in relation to which all group concepts are specific. This group of concepts reflects the hyper-hyponymy of generic relationship expressing the semantic features of the concept of “pedagogical monitoring” with varying degrees of concretization. To define terms at these levels, it is necessary to determine the essence of the term by reference to the generic term, which is located at the higher level of the generic network, the specific differences of the term from other terms located at the lower level, and an additional semantic feature that makes the content of the specific term wider than the generic one. While moving down from the term “pedagogical monitoring”, the object of monitoring is refined, from its too general notion of “educational system”, its constituent elements stand out, the objects of pedagogical monitoring in higher education are detailed. Further, the object of monitoring is detailed by isolating certain components from it. Considering that the sectoral terminological systems have a multi-level structure of generic relationships, the use of the constructed generic network provides in this case standardization of terminology and a single information and communication basis for the work of specialists in the field of research on questions of monitoring.